Study on the Driving Effect of "Sports + Tourism" Industry Integration on the High-Quality Development of Foshan City Economy - He, Dongjin; Zhou, Jiajun; Zhong, Zhengqi; Huang, Chenghe; Li, Yingmei (International Journal of Global Economics and Management, 2024)
In the context of economic globalization and regional integration, industrial integration has become a key strategy for promoting high-quality economic development. Foshan City, as an important city in Guangdong Province, has the potential to develop the "sports + tourism" industry integration with its rich sports and tourism resources. This study aims to explore how this integration can contribute to the high-quality development of Foshan’s economy, analyze its impact on economic growth, structural optimization, innovation drive and regional coordinated development, and propose corresponding policy recommendations. Through literature review, case study analysis and theoretical framework construction, this study examines the status quo, challenges and opportunities of the integration of the "sports + tourism" industry in Foshan City. The results show that industrial integration has played a positive role in promoting economic growth and structural optimization, but it also faces challenges such as insufficient vitality of market players and limited brand influence. In this regard, this study puts forward countermeasure suggestions such as optimizing the policy environment, innovating the industrial integration model, cultivating market players, strengthening branding and marketing strategies, and establishing risk management and response mechanisms. These recommendations aim to promote the in-depth integration of the "sports + tourism" industry in Foshan City and provide a new impetus for the high-quality development of the economy.